2011
DOI: 10.1002/hed.21447
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced 18F‐FDG‐PET/CT for the assessment of necrotic lymph node metastases

Abstract: Contrast-enhanced CT and contrast-enhanced ¹⁸F-FDG-PET/CT perform equally and better than non-enhanced ¹⁸F-FDG-PET/CT in detecting CLNM in tonsillar SCC. Therefore, in patients scheduled for ¹⁸F-FDG-PET/CT, we strongly suggest performing a contrast-enhanced ¹⁸F-FDG-PET/CT, which is not routine in most centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 19 publications
1
42
0
1
Order By: Relevance
“…2) (41). In a retrospective study by Haerle et al (41), 34 patients with tonsillar SCC underwent pretreatment contrast-enhanced 18 F-FDG PET/CT followed by neck dissection as a standard of reference. The enhanced CT part, 18 F-FDG PET part, nonenhanced 18 F-FDG PET/CT part, and enhanced 18 F-FDG PET/CT part were assessed separately.…”
Section: Evaluation Of Locoregional Nodal Metastasesmentioning
confidence: 99%
“…2) (41). In a retrospective study by Haerle et al (41), 34 patients with tonsillar SCC underwent pretreatment contrast-enhanced 18 F-FDG PET/CT followed by neck dissection as a standard of reference. The enhanced CT part, 18 F-FDG PET part, nonenhanced 18 F-FDG PET/CT part, and enhanced 18 F-FDG PET/CT part were assessed separately.…”
Section: Evaluation Of Locoregional Nodal Metastasesmentioning
confidence: 99%
“…46,47 Recently, there have been several reports of the possible superiority of PET/CE-CT over standard PET/CT in different clinical settings, including better local 48 and nodal analysis. 49 Other studies, 50,51 confirmed the high accuracy of nodal staging by PET/CT, in particular, if CE-CT is used during PET protocol.…”
Section: Lymph Node Involvement (Nodal Staging)mentioning
confidence: 84%
“…An interesting aspect might be that metastatic lymph nodes in our studyhadahighBF,alowBVandafastMTT.Thismightbepartly attributed to HPV-positive lymph nodes. Those nodes are generally large, but do contain a large amount of cystic/necrotic material and thus the SUV can be very low [27]. We did not evaluate PS because we used too short a protocol to measure stable PS values.…”
Section: Tumour Vs Metastatic Lymph Nodesmentioning
confidence: 99%